Compensation voltage moduli comparison-based wide-area protection algorithm independent of data synchronism and integrity - Lin, Xiangning; Ma, Shumin; Jin, Neng; Tong, Ning; Chen, Le; Li, Zhengtian; Rong, Zirui; Zhang, Peifu (IET generation, transmission & distribution, 2020)
Secondary direct-current loss within a substation is a severe event. In China, each line protection device is generally powered by one set of secondary direct current (DC) power system within a substation of 110 kV voltage level. In this case, the line protection devices will be immediately taken out of service when the secondary DC is lost, and the lines protected by them will lose their corresponding protections. Once a fault occurs on the line, only the remote back-up protection can be relied on to isolate the fault, which expands the fault influence and increases its clearance time. To handle the above problem, a novel wide-area protection algorithm based on compensation voltage moduli comparison is proposed, which is independent of multi-terminal data synchronism. Then, a comprehensive protection strategy composed of the proposed protection algorithm and the original local distances protection is proposed. The results from a power systems computer aided design/electromagnetic transients including DC (PSCAD/EMTDC)-based simulation verify that the proposed protection algorithm has higher sensitivity. The comprehensive protection strategy could cope with most line faults effectively, even if only partial data are available, the selectivity and speed of which are better than that of distance protections.